Four new species of the spider genus Pseudopoda Jäger, 2000 (Sparassidae) from Yintiaoling Natural Reserve of Chongqing, China - Deng, Ming-Qin; Zhong, Yang; Irfan, Muhammad; Wang, Lu-Yu (Zootaxa, 2023)
Four new species of the huntsmen spider genus Pseudopoda are described: P. hongqi sp. n. (male), P. shuyue sp. n. (male, female), P. wuxi sp. n. (male, female) and P. yintiaoling sp. n. (male, female). Morphological descriptions, photos of body and copulatory organs, as well as a locality map are provided.